Sperm Epigenetics and Its Impact on Male Fertility, Pregnancy Loss, and Somatic Health of Future Offsprings - Ibrahim, Yetunde; Hotaling, Jim (Seminars in Reproductive Medicine, 2018)
Sperm epigenetic programming is tailored to meet the need of this specialized cell, which include its interaction with the oocyte during fertilization and early embryo development. The unique nature of the sperm epigenome has resulted in multiple studies investigating how perturbations in epigenetics might impact male fertility and early embryo development. In addition, sperm epigenetics appear to be altered by specific environmental exposures, which could provide a link for investigating the role of these triggers in somatic health of off springs produced. This has the potential of explaining otherwise missing heritability factors seen with several diseases. While this field of investigation is new and with limited validation, it is intriguing and further studies are warranted.
Keywords: epigenetics; male infertility; pregnancy loss; transgenerational effects; somatic health